Process Skills of students’ in Doing Practicum - Aslim, Aslim; Nurhayati, Nurhayati (Indonesian Journal of Educational Studies, 2014)
The purpose of this study was to determine how much the Science Process Skills of student in conducting laboratory experiments with the initial seminar of design of experiment on course of "Secondary School Physics Practicum". This research was pre-experimental design with a one shoot case study. Data collected using the instruments of science process skills. The data analysis in this study using descriptive statistical analysis. The results of the descriptive analysis shows that science process skills students Physical Education Program can be improved through the provision of seminars initial design experiments on subjects Secondary School Physics Practicum. It can be seen from the average score of science process skills students who attend these events are in the medium category. And when viewed per aspect category, there are two aspects that are quite prominent (at the high category) which aspects: (1) designing and conducting experiments, and (2) to collect data.